Responses of some kenaf (Hibiscus cannabinus L.) varieties to root knot nematode infection - Tahery, Yaghoob (2012)
Kenaf is a fast growing crop cultivated for its natural fibre. It is one of the potential multipurpose crop species in Malaysia which thrives relatively well in less fertile BRIS (Beach Ridges Interspersed with Swales) soils. Despite growing relatively well in this area, there is a threat of infection with Root Knot Nematode (RKN) which can potentially reduce the growth and yield production of this crop. However, the knowledge on nematode infection that may affect gas exchange characteristics and enzymatic defence mechanisms of kenaf still remains limited. Moreover, as traditional method of nematode management is time consuming, laborious and associated with health and environmental concerns, thus the host resistance and screening based on molecular markers would be a preferable choice to apply. The study evaluated disease incidence of RKN and its severity on kenaf plants cultivated in sandy BRIS soils in Telaga Papan, Terengganu, Malaysia following which a subsequent screening was made on the Hibiscus cannabinus varieties for their growth, productivity, resistance, physiological and enzymatic responses to RKN infections. In addition, the study determined the genetic mode of the RKN resistance inheritance in the F2 populations those were derived from crosses of resistant and susceptible plants which was further verified by the ISSR markers which were associated with this resistance. Investigation on kenaf cultivated in BRIS soils exhibited a severe nematode infection (Meloidogyne incognita) of Race 1, which was significantly correlated with the reduction in height (R2= - 0.73), diameter (R2= - 0.60) and number of nodes (R2= - 0.70). Screening of sixteen kenaf varieties from different origin was conducted using three levels of artificial inoculation viz; 1000, 5000 and 10000 eggs per pot under controlled condition with untreated plant as control showed that the average height and stalk diameter of the infected plants were reduced by 10.62% and 9.95% respectively during harvesting time of 120 days. The effects were significantly different between varieties and time of measurement. Variety KK60 (M) outperformed the others with height (214.44 cm), stem diameter (14.19 mm) and number of nodes (52) while variety 3740 performed the poorest in terms of height (115.89 cm) and stem diameter (9.94 mm) and variety 113 produced the lowest number of nodes (32) upon RKN infection. Inoculation with M. incognita decreased kenaf height and diameter at a range of 0.37% to 24.79% and 1.4% to 16.5% respectively. Variety 113, KK60 (Aust) and Everglades 41 recorded the highest reduction in height (24.79%), diameter (16.5%) and internodes number (18.5%) respectively. On the contrary, variety 4638 recorded the least decrement in height (0.37%) and diameter (1.4%) respectively. Resistant variety (Gregg) recorded reduction in height and stalk diameter of 9.84% and 3.04% respectively while the susceptible variety (Everglades 41) produced bigger reduction of 14.55% and 8.46% for similar parameters. The highest reduction of height and diameter occurred in the third month and the first month respectively. Different varieties reacted differently with levels of nematode inoculation for all characteristics studied here. In addition, infected plants also recorded bigger losses in yield than the control. Measurement of gas exchange characteristics in infected plant showed that nematode has decreased the values of Assimilation rate (A), transpiration rate (E), intercellular CO2 concentration (ci) and Vapour Pressure Deficit based on Leaf temperature (VPDL) by 22.50%, 32.30%, 21.62% and 34.80% respectively whilst increased both water use efficiency and intrinsic water use efficiency. The different varieties used in the experiment also showed different responses of gas exchange to nematode infection. Susceptible variety showed higher assimilation rate and water use efficiency than the resistant variety. In turn, the value of stomatal closure, transpiration rate, VPDL and intrinsic water use efficiency (A: gs) for susceptible was lower than the resistant variety. Examining of individual plant based on three (3) parameters i.e. gall index ratings, egg mass index and egg per gramme root of plant showed that variety Everglades 41 is more susceptible to M. incognita Race 1 having value of 4.33, 4.89 and 16985 as compared with variety Gregg that exhibited resistance response with value of 1.67,2.33 and 2691 for the above mentioned parameters respectively. Study on biochemical basis of resistance to M. incognita in kenaf showed a significant increase of peroxidase activity in the roots of both susceptible and resistant plants when compared to the non-inoculated control plants. The resistant host exhibited five times higher peroxidase activity than the susceptible ones upon infection with nematode. Examining of resistance to RKN using gall index in F1 and F2 populations showed segregation pattern that fits the Mendelian ratio of 1: 3 (resistant: susceptible). Further investigation using sixty (60) Inter Simple Sequence Repeat (ISSR) primers revealed polymorphism between resistant and susceptible parents. Two markers ISSR 807 and ISSR 837 were found to be associated with RKN resistance trait. The phenotype variation explained by these markers accounted by 33.88% and 33.71% respectively. In conclusion, variety KK60 is the most recommended variety to be planted on sites which are proned to RKN infestation such as BRIS soils eventhough it was not found to be resistant against RKN. This is based on its overall growth performance and yield productivity upon infection with RKN. The study also revealed that screening for resistance against RKN using ISSR markers is an important reliable tool to be incorporated in kenaf improvement programme.